PSXI-23 Effect of garlic powder on supplement consumption and fly abundance in grazing cattle. (5th December 2019) - Durunna, Obioha N
Abstract: Effective pest-fly control strategies in grazing cattle will increase performance, reduce fly-borne diseases and the associated antimicrobial use. This 2-year project evaluated the effects of feeding garlic-powder to grazing cattle. Fly abundance (FA), average salt consumption (SC) and average fly avoidance behaviors (FAB, such as tail-flicks, head-throws and side-licks) were assessed in three independently-managed crossbred cow-calf groups (total=116 to 183 cow-calf pairs) within a subdivided large pasture. Each group received either salt-garlic-powder (SGP) supplement or salt (ST) only, free-choice. The SGP contained 2.1% and 5% garlic powder, respectively in both years. Fly surveys were conducted between June and September each year (approximately every 3 weeks) on cows (n = 5 to 66) randomly sampled from each group. Post-survey image analyses used digital footage and still-images of lateral views of cows and were used to evaluate resting flies (FA) on the cows and FAB. Majority were horn flies based on resting locations on the cows and close-up images. Statistical analyses were performed using generalized linear models adjusted for Year-effect. There was no treatment effect on average SC (P > 0.22) but the groups that received SGP (59g/hd/day) consumed numerically less salt-supplement than ST group (73g/hd/day). The average FA and average proportion of individuals exhibiting FAB were different (P < 0.04) between overall treatment groups where cows that received SGP had fewer flies (55 vs 125 flies) and less FAB (33% vs 42%) than the control group. However, one group that received SGP was not different (P > 0.2) from the control, suggesting that there may be differential insectifugal outcomes based on other factors. While these results suggest that infusing garlic powder into pasture trace-mineral salt does not significantly affect salt consumption and reduces the overall number of pest-flies across different grazing groups, additional studies are required to validate these findings in drylot conditions.